Management of a patient presenting with giant cell myocarditis — A case report. Issue 5 (May 2020) - Patel, Nisarg; Nooli, Nishank; Sundt, Linda
Abstract: Giant cell myocarditis is a rare and frequently fatal disease that requires extensive cardiac care. Given the rarity of this condition no specific management recommendations exist. We describe a patient who presented with congestive heart failure that required a left ventricular assist device and a temporary right ventricular assist device along with immunosuppressive therapy. This case also brings to attention how undocumented immigration status can limit transplantation opportunities in the USA. <Learning objective: Giant cell myocarditis is a rare and frequently fatal cardiac disease that, until the 1980s, was only diagnosed during autopsy. It is commonly seen in young and middle-aged, otherwise healthy, individuals with median transplant-free survival of 5.5 months from diagnosis. Current treatments with immunosuppressant medications do not seem to be significantly effective. Most patients require transplant or ventricular assist device for survival.>